The naked tree - Gendry-Kim, Keum Suk (Drawn & Quarterly, 2023)
"The year is 1951. Twenty-year-old wallflower Lee Kyung ekes out a living at the US Post Exchange, where goods and services of varying stripe are available for purchase. She peddles hand-painted portraits on silk handkerchiefs to soldiers passing through. When a handsome young northern escapee and erstwhile fine artist is hired despite waning demand, an unlikely friendship blossoms into a young woman's first brush with desire against the backdrop of the Korean War at its most devastating."--